2022
DOI: 10.1002/bco2.206
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of reported association studies of monogenic genes and bladder cancer risk and confirmation analysis in a large population cohort

Abstract: Objectives: To evaluate which of previously reported monogenic genes are associated with increased bladder cancer risk, we reviewed published papers on associations of genes and bladder cancer risk and performed a confirmation study of these genes in a large population-based cohort. Subjects and methods:A systematic review of published papers prior to June 2022 was performed first to identify all genes where germline mutations were associated with bladder cancer risk. The associations of these candidate genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(66 reference statements)
0
0
1
Order By: Relevance
“…It was challenging to undertake replication analysis utilizing the UK Biobank (UKBB), a representative European ethnic cohort, in the current study. A review of papers on BLCA biomarkers using the UKBB [ 46 – 48 ] revealed no matching results on SNP identified in our investigation, and no BLCA-metabolome studies based on UKBB were found. Consequently, our findings could be confined to this population; further studies on other races are needed.…”
Section: Discussioncontrasting
confidence: 65%
“…It was challenging to undertake replication analysis utilizing the UK Biobank (UKBB), a representative European ethnic cohort, in the current study. A review of papers on BLCA biomarkers using the UKBB [ 46 – 48 ] revealed no matching results on SNP identified in our investigation, and no BLCA-metabolome studies based on UKBB were found. Consequently, our findings could be confined to this population; further studies on other races are needed.…”
Section: Discussioncontrasting
confidence: 65%
“…It is important to note that this is not a population-based study, and the homogenous nature of the patients affects the generalizability of the results. Mian et al 16 took this analysis further by identifying the PVs significantly associated with bladder cancer risk. In their results, CHEK2, ATM, and BRCA2 were most frequently implicated, as well as MLH1 and MSH2.…”
mentioning
confidence: 99%
“…In their results, CHEK2, ATM, and BRCA2 were most frequently implicated, as well as MLH1 and MSH2. 16 In a similar study by Carlo et al, 17 586 patients with advanced UC were prospectively sequenced to identify PVs. A total of 80 patients (14%) showed moderate to high-penetrance actionable PV in BRCA2 (n 5 9), MSH2 (n 5 8), BRCA1 (n 5 8), CHEK2 (n 5 6), ERCC3 (n 5 4), and NBN and RAD50 (n 5 3).…”
mentioning
confidence: 99%